THE EFFECT OF RICE PRICE ON THE INDONESIAN INFLATION IN A NEW INSTITUTIONAL ECONOMIC PERSPECTIVE - Novita, Dian; Suharno, Suharno; Nurmalina, Rita; Nuryantoro, Nunung (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
The aim of this research is to identify and verify whether rice prices do play a role in driving national inflation using time series data. The time series data for this study spans from 2017 to 2023 on a monthly basis. To facilitate our analysis, we subject the data to standardized stationary tests, serving two essential purposes. Firstly, these tests ascertain the constancy of mean, standard deviation, variance, and covariance for each observation. Secondly, they aid in determining the extent of integration among the variables under scrutiny. For this particular purpose, we employ the Augmented Dickey-Fuller Test for Unit Roots. The outcomes of these stationary tests provide crucial insights, directing policy decisions to effectively address the challenge of inflation. It is widely acknowledged that the factors driving inflation rates, not only in Indonesia but globally, can be classified into two primary categories, the first being associated with the money supply. The research findings distinctly demonstrate that while rice certainly plays a role, it is not the exclusive or singular underlying cause of fluctuations in the inflation rate.